Vertical Grammatical Variability in Writing: Does Scaffolding Make a Difference? - Abbasi Mojdehi, Hamed; Ali Zarei, Abbas (BELT - Brazilian English Language Teaching Journal, 2023)
The present study aimed to investigate the effects of scaffolding techniques on eliminating the grammatical variability in IELTS. 120 IELTS candidates were selected randomly and placed in a control, and three experimental groups. Prior to the course, the candidates and teachers were interviewed regarding the effectiveness of scaffolding techniques. The teachers were also asked to keep a diary and report every session. On the first, 10th, 20th, and 30th sessions, three essay writing topics were given to all the candidates, and their grammatical accuracy and variability were rated by official IELTS Mock examiners to check their vertical grammatical variability. The results were analyzed using SPANOVA procedure. The qualitative data were also content analyzed, coded, and compared with the quantitative results. The findings showed that the distributed scaffolding group was relatively more successful. The qualitative results showed gaps between teachers’ and candidates’ conceptions. The theoretical and pedagogical implications are also discussed.